Connexin43 hemichannel block inhibits NLRP3 inflammasome activation in a human retinal explant model of diabetic retinopathy. (January 2021) - Louie, Henry H.; Shome, Avik; Kuo, Charisse YJ.; Rupenthal, Ilva D.; Green, Colin R.; Mugisho, Odunayo O.
Abstract: Diabetic retinopathy (DR), the most common ocular complication associated with diabetes, is a chronic vascular and inflammatory disease that leads to vision loss. The inflammasome pathway, a key part of the innate immune system, is required to activate chronic inflammation in DR. Unfortunately, current therapies for DR target pathological signs that are downstream of the inflammasome pathway, making them only partly effective in treating the disease. Using in vitro and in vivo DR models, it was discovered that connexin43 hemichannel blockers can inhibit activation of the inflammasome pathway. However, those studies were conducted using in vitro cell culture and in vivo animal disease models that are predictive but do not, of course, like any model, completely replicate the human condition. Here, we have developed an addition to our armamentarium of useful models, an ex vivo human organotypic retinal culture model of DR by exposing human donor retinal explants to a combination of high glucose (HG) and pro-inflammatory cytokines, interleukin-1 beta (IL-1β) and tumour necrosis factor alpha (TNF-α). We hypothesized that in this model, connexin43 hemichannel block would protect against NLRP3 inflammasome complex assembly which would in turn decrease signs of inflammation characteristic of DR. To test our hypothesis, molecular changes in the inflammatory and inflammasome pathway were assessed using immunohistochemistry and a Luminex cytokine release assay. Our results showed that the human retinal explant DR model was associated with increased inflammation and activation of the inflammasome pathway, characteristic of the human condition. Furthermore, we showed that by blocking connexin43 hemichannels with the hemichannel modulator, tonabersat, we were able to prevent NLRP3 inflammasome complex assembly, Müller cell activation, as well as release of pro-inflammatory cytokines and VEGF. This further supports the possible use of connexin43 hemichannel blockers as potential new therapies for DR. Highlights: The inflammasome pathway is activated in a human retinal explant model of diabetic retinopathy. Connexin43 hemichannel block prevents inflammasome activation in the human retina explant model. Connexin43 hemichannel block inhibits inflammatory cytokine release in the human retinal explant model.